Алмазный эндшпиль: [роман] / Елена Михалкова - Михалкова Елена Ивановна (Настоящий детектив, 2017)
Экземпляры: ф.12 (20180517) / Инвентарный номер: 58360 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 69 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44